Phytoplankton Stimulation in Frontal Regions of Benguela Upwelling Filaments by Internal Factors - Wasmund, Norbert; Siegel, Herbert; Bohata, Karolina; Flohr, Anita; Hansen, Anja; Mohrholz, Volker (Frontiers in Marine Science, 2016)
Filaments are intrusions of upwelling water into the sea, separated from the surrounding water by fronts. Current knowledge explains the enhanced primary production and phytoplankton growth found in frontal areas by external factors like nutrient input. The question is whether this enhancement is also caused by intrinsic factors, i.e. simple mixing without external forcing. In order to study the direct effect of frontal mixing on organisms, disturbing external influx has to be excluded. Therefore mixing was simulated by joining waters originating from “inside” and “outside” the filament in mesocosms (“tanks”). These experiments were conducted during two cruises in the northern Benguela upwelling system in September 2013 and January 2014. The mixed waters reached a much higher net primary production and chlorophyll a (chla) concentration than the original waters already 2-3 days after their merging. The peak in phytoplankton biomass stays longer than the chla peak. After their maxima, primary production rates decreased quickly due to depletion of the nutrients. The increase in colored dissolved organic matter (CDOM) may indicate excretion and degradation. Zooplankton is not quickly reacting on the changed conditions. We conclude that already simple mixing of two water bodies, which occurs generally at fronts between upwelled and ambient water, leads to a short-term stimulation of the phytoplankton growth. However, after the exhaustion of the nutrient stock, external nutrient supply is necessary to maintain the enhanced phytoplankton growth in the frontal area. Based on these data, some generally important ecological factors are discussed as for example nutrient ratios and limitations, silicate requirements and growth rates.